Brief Review: Effects of Isometric Strength Training on Strength and Dynamic Performance - Lum, Danny; Barbosa, Tiago M. (International Journal of Sports Medicine, 2019)
This review used a narrative summary of findings from studies that focused on isometric strength training (IST), covering the training considerations that affect strength adaptations and its effects on sports related dynamic performances. IST has been shown to induce less fatigue and resulted in superior joint angle specific strength than dynamic strength training, and benefited sports related dynamic performances such as running, jumping and cycling. IST may be included into athletes’ training regime to avoid getting overly fatigue while still acquiring positive neuromuscular adaptations; to improve the strength at a biomechanically disadvantaged joint position of a specific movement; to improve sports specific movements that require mainly isometric contraction; and when athletes have limited mobility due to injuries. To increase muscle hypertrophy, IST should be performed at 70–75% of maximum voluntary contraction (MVC) with sustained contraction of 3–30 s per repetition, and total contraction duration of>80–150 s per session for>36 sessions. To increase maximum strength, IST should be performed at 80–100% MVC with sustained contraction of 1–5 s, and total contraction time of 30–90 s per session, while adopting multiple joint angles or targeted joint angle. Performing IST in a ballistic manner can maximize the improvement of rate of force development.
Keywords: musculotendinous stiffness; rate of force development, muscle hypertrophy; joint angle, static strength training